Early aortic valve replacement improves exercise capacity in truly asymptomatic patients with severe aortic stenosis. (3rd October 2022) - Banovic, M; Boskovic, N; Bojanic, M; Nedeljkovic, I; Jovanovic, M; Penicka, M; Bartunek, J
Abstract: Background: Exercise capacity is a strong predictor of morbidity and mortality overall. In severe aortic stenosis (AS) ustained pressure overload during watchful waiting is associated with LV structural and functional deterioration and impaired clinical outcome both pre- and post aortic valve replacement (AVR). The effect of early surgical aortic valve replacement (SAVR) in asymptomatic patients with severe AS and normal left ventricular function on exercise capacity in unknown. Aim: We investigated whether the early surgical AVR in truly asymptomatic patients with severe aortic stenosis and normal LVEF improves the exercise capacity. Methods: This is a sub-analysis or the AVATAR trial (NCT02436655), which is international prospective randomized controlled trial that evaluated the safety and efficacy of early SAVR in the treatment of asymptomatic patients with severe AS, according to common criteria (valve area ≤1 cm 2 with aortic jet velocity >4 m/s or a mean transaortic gradient ≥40 mm Hg), and with normal left ventricular function. Patients underwent cardiopulmonary exercise testing (supine bicycle, ramp protocol, 15 W/min) at the baseline and 12 months following the randomization. Patients who had positive exercise testing at baseline visit were excluded. We compared the value of workload (in WATs), VO2 max, VO2 AT, VE/VCO2 and PETCO2 slope at the inclusion and at 12 months. Results: Total of 157 patients (mean age, 67 years; 57% men) were randomly allocated to early surgery (n=78) or conservative treatment (n=79). Mean LVEF and Vmax in early surgery and conservative treatment group were 70% and 4.5m/s and 69% and 4.5m/s, respectively. After 12 months in patients with conservative treatment there was a slight decrease in the values of workload, VO2 max, VO2 AT, VE/VCO2 and PETCO2 slope, but without statistical significance. However operated patients showed a significant increase in workload (115.4±38.4 watts at 12 months vs 104.8±42.2 at inclusion, p=0.038) and VO2 max (19.7±6.8 at 12 months vs 16.2±5.4 at the inclusion, p=0.048), while there was slight increase in the values of VO2 AT, VEVCO2 and PETCO2 but without statistical significance. Conclusion: Early SAVR improve the functional capacity in asymptomatic patients with severe aortic stenosis and normal left ventricular ejection fraction Funding Acknowledgement: Type of funding sources: None.